A new method for durability dependance of a cutting tool on a cutting speed - Karol Vasilko (Communications - Scientific letters of the University of Zilina, 2000)
In the entire history of the development of the metal cutting theory Taylor’s whhich appeared in 1905, has been used to describe the relation between a cutting tool durability and a cutting speed. This relation was established in 1905. This work presents the analysis of the up to now attempts carried out to improve the mentioned relation. The submitted proposal results in the method of creation of the Tvrelation, which provides a much better identity with the experiment. In the second part of the work the method is verified experimentally on aseries of experimental results.